Development of scale to measure the perception of multistakeholders towards potential of dairy and goat production system for augmenting farmers’ income - pathade, Santosh S; Singh, B P; Verma, M R; Pordhiya, K I (Indian Journal of Dairy Science, 2020)
Livestock sector is an important sub sector of agriculture of Indian economy. The highest growth in income is registered in receipts from livestock farming and it has increased its share in total income of a farm household from 4 per cent to 13 per cent during 2003-2013. (Report of committee on DFI, 2017). Thus, there is need to put special attention towards the potential of livestock sector. In this direction the research was designed with the objective of developing equal appearing interval scale to measure perception of multistakeholders towards potential of dairy and goat production system. A list of 49 statements indicating positive and negative perception was considered for dairy and goat production system respectively. The statements were then scrutinised and edited by applying criteria and guidelines suggested by Thurstone and Chave (1929).The judges’ response was recorded on seven point continuum. The score was summed up to calculate scale and Q value for each statement. Final statements were selected on the basis of scale value (>1.60) and Q value (<1.60). The response of Stakeholders (LDOs, ACAH from Dept of Animal Husbandry and SMS of KVKs was recorded on three point continuum. The total individual respondent score was calculated by summing up the score of each statement given by individual. The scale so developed finally consist of 20 statements (11 positive and 9 negative) for dairy and 14 (8 positive and 6 negative) for goat production system. The reliability for whole scale calculated using Spearman brown formula and was found to be 0.90 and 0.86 for dairy and goat production system respectively, which is significant at 1 per cent level of significance.